The economic burden of malaria inpatients and its determinants during China's elimination stage - Chen, Fangfei; Chen, Xiaoyu; Gu, Peng; Sang, Xiaodong; Wu, Ruijun; Tian, Miaomiao; Ye, Yisheng; Long, Chengxu; Bishwajit, Ghose; Ji, Lu; Feng, Da; Yang, Lei; et al. (Frontiers in Public Health, 2022)
Background Malaria burden is still worrisome, while empirical evidence from malaria-eliminated countries including China may provide inspiration for the world. Objective This study aimed to investigate China's malaria hospitalization costs and explore its determinants. Methods Stratified multistage sampling across provincial, municipal, and county hospitals was conducted in 2017. All the malaria medical records were retrieved from 2014 to 2016 in 70 hospitals. Parametric and non-parametric methods were employed to estimate hospitalization costs, and the non-parametric bootstrap was used to compare hospitalization costs among sample areas and assessed the uncertainty of its differences. Quantile regressions were conducted to identify the determinants of hospitalization costs. Results The median hospitalization costs of 1633 malaria inpatients were 628 USD. Medication and laboratory tests accounted for over 70% of total expenditure. The median reimbursement rate was 41.87%, and this number was even lower in higher-level hospitals (<35%) and among the New Rural Cooperative Medical Scheme (<40%). Finally, health insurance type, hospital tier, clinical units, unknown fever, and comorbidity were the main determinants of hospitalization costs. Conclusion The disparity of health protection for malaria hospitalization between rural and urban areas was noteworthy. Equivocal diagnosis and comorbidity are contributors of high cost as well. A reasonable payment system and enhanced capacities to treat malaria in a cost-effective way are suggested to reassure malaria economic burden.